Implementasi Pendekatan Contextual Teaching and Learning pada Pembelajaran Qur’an Hadits - Suriadi Suriadi; Triyo Supriyatno; Muhammad Walid (Jurnal Educative: Journal of Educational Studies, 2020)
This article discusses the learning of the Qur'an with the approach of contextual teaching and learning. This research was conducted at the Islamic Junior High School Muhammadiyah Sejangkung Sambas Regency. The study focused on learning the Qur'anic Hadith. The aim of the research was to describe the contextual teaching and learning on: a) the implementation of the learning of the Qur'anic Hadith, b) the implications of learning the Qur'an Hadith, (c) the factors supporting and inhibiting the learning of the Hadith Qur'an. This research was designed with a qualitative approach. The subject of the research was the Hadith teacher and the students at the Islamic Junior High School Muhammadiyah. The results of the analysis show that the implementation of the learning of Qur'an Hadith with a contextual teaching and learning approach is achieved by conveying more actual, realistic, enjoyable material in the four forms of learning methods namely learning together, group discussion, Jigsaw, and peer teaching method. Implications of learning have a very positive impact on students, among others, students are more responsive to the material being delivered, the classroom atmosphere is more pleasant, the material being delivered is more actual, so that it can indirectly improve the quality of education in madrasah (Islamic junior high school). The supporting factors for the positive effects are as follows: (1) The ability of teachers, (2) the ability of students, (3) facilities and infrastructure;  while the inhibiting factors in implementing this strategy are (1) the limitations of teachers, (2) the lack of facilities and infrastructure, and (3) the diverse psychological abilities and souls of students Artikel ini membahas tentang pembelajaran qur’an hadits dengan pendekatan contextual teaching and learning. Penelitian ini dilakukan di madrasah Tsanawiyah Muhammadiyah Sejangkung Kabupaten Sambas. Kajian difokuskan pada pembelajaran qur’an hadits. Penelitian bertujuan untuk menguraikan pembelajaran contextual teaching and learning pada: a) implementasi pembelajaran Qur’an Hadits, b) implikasi pembelajaran Qur’an Hadits, (c) faktor pendukung dan penghambat pembelajaran Qur’an Hadits. Penelitian ini didesain dengan pendekatan kualitatif. Subjek penelitian guru Qur’an Hadits dan siswa di madrasah Tsanawiyah Muhammadiyah Sejangkung. Hasil analisis menunjukkan bahwa implementasi pembelajaran qur’an hadits dengan pendekatan contextual teaching and learning terwujud dilakukan dengan cara menyampaikan materi yang lebih aktual, lebih realistis, lebih menyenangkan dalam empat bentuk metode pembelajaran yaitu metode belajar kelompok (learning together), metode diskusi kelompok (group discussion), metode Jigsaw dan metode tutor sebaya (peer teaching). Implikasi pembelajaran memberikan dampak yang sangat positif terhadap siswa antara lain siswa lebih mudah menerima materi yang disampaikan, suasana kelas lebih menyenangkan, materi yang disampaikan lebih aktual, sehingga secara tidak langsung) dapat meningkatkan mutu pendidikan di madrasah. Sedangkan faktor pendukung (1) Kemampuan guru, (2) Kemampuan siswa, (3). Sarana dan prasarana. Sedangkan faktor penghambat dalam penerapan Pendekatanini adalah: (1) Keterbatasan guru, (2), Sarana dan prasarana yang kurang memadahi, (3) Kemampuan dan jiwa psikologis siswa yang beragam